Effect of Seed Coat Removal Treatments on Seed Germination and Seedling Attributes in Mango Varieties. Issue 1 (2nd January 2016) - Muralidhara, B. M.; Reddy, Y. T. N.; Srilatha, V.; Akshitha, H. J.
ABSTRACT: A field experiment was carried out at the Indian Institute of Horticultural Research, Bengaluru during 2011–12 to study the effect of seed coat removal on seed germination and vigor of polyembryonic mango seedlings. In seed coat removal, the cultivar Muvandan recorded the maximum germination percent (85.4%), extent of polyembryony (2.76), and maximum number of leaves (10.3), whereas Bappakkai recorded maximum plant height (22.4 cm), stem girth (0.64 cm), leaf area (249.2 cm 2 ), fresh weight (18.5 g) and dry weight (8.4 g), vigor index-I (1831.5 cm), and vigor index-II (685.7 g). With respect to treatments, seed coat removal was superior in all of the parameters, namely, initiation of germination (16.7 days), germination percent (78.3%), extent of polyembryony (2.50), plant height (19.5 cm), stem girth (0.62 cm), number of leaves per plant (8.7), leaf area (288.3 cm 2 ), fresh weight (16.2 g) and dry weight (7.3 g), vigor index-I (1559.0 cm), and vigor index-II (581.8 g) compared to seed coat intact. There were no significant differences among the interactions of different treatments and cultivars.